A new phenolic compound from Phedimus middendorffianus with antiproliferative activity. Issue 12 (17th June 2020) - Lee, Jiho; Woo, Sunmin; Sung, Sang Hyun; Yang, Heejung
Abstract: A new phenolic compound (1 ) and together with 12 known compounds–eight flavonoids (2  ∼ 9 ), two phenolic compounds (10 and 11 ) and two benzoic acid (12 and 13 )–were isolated from Phedimus middendorffianus (Maxim.). The structures of all compound were determined on the basis of spectroscopic (MS and NMR) analyses. Compounds 4, 5, 7 and 11 ∼ 13 were showed anti-proliferative activities against MCF-7 than PC-3 cell line. Also compound 12 and 13 showed the significant cytotoxic activities against two cancer cell lines, PC-3 and MCF-7. Graphical abstract: